The Significance of the Current Account : Implications of European Financial Integration - Molho, Lazaros (IMF Working Papers; Working Paper ;, 1990)
This paper reasseses the significance of persistent current imbalances as they become easier to finance in the process of European integration. After highlighting some limitations of simple saving-investment guidelines for policies toward the current account, the paper shows that an economy's current account position may be an indicator of its attitude toward risk. Externalities in the incidence of risk could warrant government concern over current imbalances, even if they are caused by privately motivated investment and saving decisions. Such externalities may arise from credit markets' conventional perceptions about country risk and from existing deposit insurance arrangements.